Graphene oxide and carbon nanotube-based saturable absorber q-switched erbium doped fiber laser / Rawan M S Soboh - Rawan, M S Soboh (2018)
To date, various Q-switched Erbium doped fiber lasers (EDFLs) have been demonstrated using various types of nanomaterials based saturable absorber (SA) such as graphene, topological insulators, transition metal dichalcogenides. In this report, Q-switched EDFLs have been demonstrated two types of SAs; graphene oxide (GO) and carbon nanotube (CNT) films. The CNT and GO based SA was successfully fabricated by embedding the nanoparticles into polyethylene oxide (PEO) and polyvinyl alcohol (PVA), respectively. Both films were characterized by FESEM and XRD. The CNT based Q-switched EDFL produces a pulse train operating at 1559.04 nm. The repetition rate of the pulse train is tunable within 31.5 kHz to 55.04kHz as the pump power is varied from 0 mW to 28.38 mW. The maximum pulse energy of 47.7834 nJ and the lowest pulse width of 5 μs were obtained at the pump power of 28.38 mW. The RF spectrum of the pulse train shows signal to noise ratio of about 74 dB, which indicates the stability of the laser. On the other hand, GO based EDFL produces a stable Q-switching pulse operating at 1558.186 nm at threshold pump power of -2.49mW. The repetition rate of the laser varies from 22.32 kHz and 69.83 kHz as the 980-nm pump power increased from -2.49 mW to 28.38 mW. The Q-switching operating has the shortest pulse width of 5 μs, the maximum pulse energy up to 98.73 nJ and the peak-to-pedestal ratio of 70 dB indicating the high stability of the laser. These results indicate that GO film performed better than CNT in terms of lower threshold pump power and better stability. Both SA have a great potential for pulse generation at 1.5 μm.